Effect of long-term manganese exposure on oxidative stress, liver damage and apoptosis in grouper Epinephelus moara ♀ × Epinephelus lanceolatus ♂ - Wang, Xi; Liu, Bao-Liang; Gao, Xiao-Qiang; Fang, Ying-Ying; Zhang, Xian-Hong; Cao, Shu-Quan; Zhao, Kui-Feng; Wang, Feng (Frontiers in Marine Science, 2022)
Manganese (Mn) is an indispensable trace element , however, it may occur at high concentrations in water and sediments of aquatic ecosystems due to natural and anthropogenic activities, and it can interfere with physiological and biochemical mechanisms in fish. This study was conducted to determine toxic effects of exposure to Mn2+ (0, 0.5, 1, 2, and 4 mg/L) for 30 d regarding liver damage and apoptosis in Yunlong grouper (Epinephelus moara♀×E. lanceolatus♂). Expression of superoxide dismutase and catalase genes in the liver was significantly increased days 10 and 20 following exposure to Mn2+ (4 mg/L), but was reduced on day 30. Similarly, expression of glutathion peroxidase and glutathione reductase genes was elevated after 10 days of exposure to 2 and 4 mg/L Mn2+, but decreased after 20 and 30 days. After 30 days of exposure to high concentrations of Mn2+, liver tissue showed hepatic sinusoidal gap congestion, dilatation, cell vacuolation and necrosis. In addition, the activities of alanine aminotransferase and aspartate transaminase as well as 8-hydroxydeoxyguanosine levels were significantly increased after Mn2+ exposure. Moreover, Mn2+ exposure altered the expression pattern of some pivotal genes associated to apoptosis (p53, bax, bcl-2, apaf-1, caspase-9 and caspase-3), which suggested that Mn2+ exposure induces apoptosis through the mitochondrial pathway. The above results showed that excessive Mn2+ induced apoptosis and liver damage in grouper through eliciting oxidative stress. These insights help elucidate the mechanism by which Mn induces toxicity in marine fish, and they provide a new perspective regarding the detrimental effects of heavy metals in fish.